2020
DOI: 10.3390/biom11010024
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin N-glucosides: Occurrence, Metabolism and Biological Activities in Plants

Abstract: Cytokinins (CKs) are a class of phytohormones affecting many aspects of plant growth and development. In the complex process of CK homeostasis in plants, N-glucosylation represents one of the essential metabolic pathways. Its products, CK N7- and N9-glucosides, have been largely overlooked in the past as irreversible and inactive CK products lacking any relevant physiological impact. In this work, we report a widespread distribution of CK N-glucosides across the plant kingdom proceeding from evolutionary older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 81 publications
1
12
0
Order By: Relevance
“…Despite this, the hormonal spectra mostly corresponded with those in M5 embryos, especially in the case of ABA derivatives and auxins. However, in contrast to SEs, ZEd also contained cytokinin N -glucosides ( N9 - but not N7 -glucosides), apparently irreversible forms widely distributed throughout the plant kingdom ( Pokorná et al, 2021 ). Very low concentrations of phytohormones in Norway spruce ZEd suggest a possible correlation between the minimum WC in these winter seeds and their low biochemical activity, which seems to be related to the deep dormancy of Norway spruce seeds during the winter season.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the hormonal spectra mostly corresponded with those in M5 embryos, especially in the case of ABA derivatives and auxins. However, in contrast to SEs, ZEd also contained cytokinin N -glucosides ( N9 - but not N7 -glucosides), apparently irreversible forms widely distributed throughout the plant kingdom ( Pokorná et al, 2021 ). Very low concentrations of phytohormones in Norway spruce ZEd suggest a possible correlation between the minimum WC in these winter seeds and their low biochemical activity, which seems to be related to the deep dormancy of Norway spruce seeds during the winter season.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of DZ-types has also been observed in anthers of rice (Hirano et al, 2008), and the lack of these CK-types appears to be characteristic of some evolutionarily older non-vascular plants (e.g., Stirk et al, 2003;Záveská Drábková et al, 2015;Žižková et al, 2017). In Arabidopsis seedlings, Hošek et al (2020) showed that DZtype CKs are metabolically independent of other CK metabolic pathways, indicating their low abundance (e.g., Pokorná et al, 2021) compared with iP-or tZ-types, which might also be related to tobacco pollen.…”
Section: Discussionmentioning
confidence: 97%
“…Both benzyladenine and kinetin are adenine-type cytokinins with a similar chemical structure, but in BA, a benzyl group can be found instead of the furfuryl group. It is noteworthy that senescence was delayed by kinetin and BA in an oat leaf test, but not by natural cytokinins, zeatin, and isopentenyl adenine [8]. In addition, both benzyladenine and kinetin show antioxidant properties in human skin fibroblast and in mammalian cells [9,10].…”
Section: Introductionmentioning
confidence: 94%